English as a Medium of Instruction in Learning Professional Skills for Engineers - Adrián Peñate Sanchéz (Universitat Jaume I. Department of English Studies, 2021)
In this article, we reflect on the variables to be considered when teaching in English a subject of the bachelor's degree of Computer Engineering: "Learning Professional Skills for Engineers". In order to make this study, we start from an analysis of the recent history of teaching in English at university level and the institutional context in which it happens. Three research questions are posed, with the intent to check what minimum conditions must be met to be able to teach this subject in English. The results lead us to conclude that the option of English as a Medium of Instruction (EMI) is not the appropriate one, taking into account both the linguistic and didactic training of the teaching staff and the language accreditation of the students. However, it is feasible to opt for the Integrating Content and Language in Higher Education (ICLHE) option.